# Aritmetiske serier

## Sum

Har følgende omskrivning: $$\sum_{k=1}^{n} k = \frac{n(n + 1)}{2}$$

Bevis Induktionsstart: $$n_1 = \frac{1 \cdot 2}{2} = 1$$ $$n_2 = 1 + 2 = 3 = \frac{2 \cdot 3}{2}$$ Induktionsskridt, Lad $$\sum_{k=1}^{n} = \frac{n(n + 1)}{2}$$ Vi får $$\sum_{k = 1}^{n + 1} k =$$ $$\sum_{k = 1}^{n} k + n + 1 =$$ $$\frac{n(n + 1)}{2} + n + 1 =$$ $$\frac{n(n + 1) + 2n + 2}{2} =$$ $$\frac{n^2 + 3n + 2}{2} =$$ $$\frac{(n + 1)(n + 2)}{2}$$ Og vi har vist hvad vi skulle.

Kan skrives som: $$\sum_{k=0}^{n} k^{2} = \frac{n(n + 1)(2n + 1)}{6}$$
Bevis Induktionsstart: $$n_1 = 1^2 = \frac{1 \cdot 2 \cdot 3}{6} = 1$$ $$n_2 = 1^2 + 2^2 = 5 = \frac{2 \cdot 3 \cdot 5}{6}$$ Induktionsskridt, lad $$\sum_{k = 0}^{n} k^{2} = \frac{n(n + 1)(2n + 1)}{6}$$ Vi får: $$\sum_{k = 0}^{n} k^{2} + (n + 1)^2 =$$ $$\frac{n(n + 1)(2n + 1)}{6} + (n + 1)^2 =$$ $$\frac{n(n + 1)(2n + 1) + 6(n + 1)^2}{6} =$$ $$\frac{(n(2n + 1) + 6(n + 1))(n + 1)}{6} =$$ $$\frac{(2n^2 + 7n + 6)(n + 1)}{6} =$$ $$\frac{(n + 2)(2n + 3)(n + 1)}{6} =$$ $$\frac{(n + 2)(2n + 3)(n + 1)}{6} =$$ $$\frac{(n + 1)(n + 2)(2(n + 1) + 1)}{6}$$ Og vi har vist hvad vi skulle.
Kan skrives som: $$\sum_{k=0}^{n} k^{3} = \frac{n^2(n + 1)^2}{4}$$
Bevis Induktionsstart: $$n_1 = 1^3 = 1 = {1 \cdot 4}{4}$$ $$n_2 = 1^3 + 2^3 = 9 = {4 \cdot 9}{4}$$ Induktionsskridt, lad $$\sum_{k=0}^{n} k^{3} = \frac{n^2(n + 1)^2}{4}$$ Vi får $$\sum_{k = 0}^{n} k^{3} + (n + 1)^3 =$$ $$\frac{n^2(n + 1)^2}{4} + (n + 1)^3 =$$ $$\frac{n^2(n + 1)^2 + 4(n + 1)^3}{4} =$$ $$\frac{(n^2 + 4(n + 1))(n + 1)^2}{4} =$$ $$\frac{(n^2 + 4n + 4)(n + 1)^2}{4} =$$ $$\frac{(n + 1)^2(n + 2)^2}{4}$$ Og vi har vist hvad vi skulle.